1990
DOI: 10.1021/j100379a049
|View full text |Cite
|
Sign up to set email alerts
|

Isolated redox centers within microporous environments. 1. Cobalt-containing aluminophosphate molecular sieve five

Abstract: Cobalt-containing aluminophosphate five (CoAPO-5) was synthesized and shown to contain tetrahedral Co2+ residing within framework atomic positions and also as extraframework cations. The isolated framework Co2+ atoms can be oxidized by 02 at 500 °C to Co3+ which is stabilized in tetrahedral coordination by the oxide lattice. The framework Co3+ is easily reduced to Co2+ by a variety of reducing agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
78
1
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 0 publications
9
78
1
1
Order By: Relevance
“…The spectra for fresh, air-treated and H 2 -treated CoAPO-5 and CoAPO-18 resemble those previously reported for CoAPO-5 12,13 and CoAPO-18. 24,25 Low-energy spectral features have been assigned to Co 2+ , but their sensitivity to coordination symmetry remains unclear, because multiple complex electronic transitions are available in both tetrahedral and octahedral Co 2+ complexes.…”
Section: Chemical and Structural Changes Insupporting
confidence: 86%
See 1 more Smart Citation
“…The spectra for fresh, air-treated and H 2 -treated CoAPO-5 and CoAPO-18 resemble those previously reported for CoAPO-5 12,13 and CoAPO-18. 24,25 Low-energy spectral features have been assigned to Co 2+ , but their sensitivity to coordination symmetry remains unclear, because multiple complex electronic transitions are available in both tetrahedral and octahedral Co 2+ complexes.…”
Section: Chemical and Structural Changes Insupporting
confidence: 86%
“…All MeAPO-5 and MeAPO-18 samples showed X-ray diffraction patterns for the expected crystal structure. 12,13 Very weak diffraction lines for trace crystalline impurities were detected only in CoAPO-5; these appear at angles corresponding to the most intense lines for AlPO-18, indicating the presence of ∼1% AlPO-18 crystals in this sample.…”
Section: Synthesis and Characterization Of Meapo Samplesmentioning
confidence: 86%
“…The increased weight loss of metal-containing AlPO-5s at higher temperatures clearly indicated that there existed strong interactions between the framework of MeAPO-5s and the template, which made TEA molecules strongly bonded in MeAPO-5s. Other authors [16][17][18] have also observed the similar experimental results for metal-containing aluminophosphate molecular sieves (Me = Co, Mn, V, etc.). This is usually taken as a proof that charge deficiency had been induced in the framework by isomorphous substitution of transition metals.…”
Section: Thermal Analysissupporting
confidence: 67%
“…1 shows XRD patterns of as-synthesized AlPO 4 -5, calcined AlPO 4 -5 and 0.4 % Rh loaded AlPO 4 -5. The XRD patterns of these samples correspond well with that for reported AlPO 4 -5 structure and do not show any impurity [21][22][23][24][25][26]. Upon calcination, a little increase in intensities of XRD patterns were observed due to little increased particle size.…”
Section: Resultssupporting
confidence: 84%